Peran Humas BAKTI dalam Memperbaiki Reputasi Instansinya dan Reputasi Kementerian Kominfo: Studi Kasus Isu Korupsi Pembangunan BTS 4G Tahun 2023 - Frima, Randyansyah; Santri, Ghugus (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The impressive pace of digital transformation development over the past ten years has ironically only occurred in big cities in Indonesia. With internet penetration still uneven, it has created disparities in access to telecommunications infrastructure in rural areas of Indonesia. In fact, the development of communication technology has an important role. To overcome various existing gaps, BAKTI was formed as a Work Unit at the Ministry of Communication and Information Technology tasked with providing telecommunications and informatics infrastructure and services in the 3T Region. In carrying out its duties and functions, BAKTI strives to create a positive reputation for fast and good government performance. However, in 2023, a crisis occurred at the Ministry of Communication and Information Technology and at BAKTI, namely the corruption case of the 4G BTS construction project and supporting infrastructure for packages 1, 2, 3, 4, and 5. In dealing with a crisis situation that occurs, appropriate crisis management and crisis communication is needed to restore the agency's reputation and increase public trust. The Public Relations Team plays an important and strategic role in overcoming the crisis and protecting the reputation of its Government Institution. In line with this, the focus of this study is to analyze the role of the BAKTI Public Relations team in handling crisis conditions and improving the Government Institution's reputation during the 2023 4G BTS Construction Corruption Case. This study uses a qualitative method, constructivism paradigm, and a case study approach. The data collection technique in this study uses in-depth interviews, and is also supported by secondary data through literature studies obtained from online news.